The effect of parasitism on clover root weevil flight capability - Eden, T.M.; Donald, M.; Gerard, P.J. (New Zealand Plant Protection, 2008)
The Irish strain of Microctonus aethiopoides was released in New Zealand in 2006 to help suppress populations of the clover pest clover root weevil (Sitona lepidus) A study was undertaken to determine if this parasitoid will be passively dispersed through flight activity by parasitized hosts In the laboratory Irish M aethiopoides parasitized equally hosts with or without flight muscles and subsequent presence of parasitoid eggs or first instar larvae had no effect on the propensity for S lepidus to prepare to take flight during laboratory observations In the field significantly fewer clover root weevil with flight muscles were found to be parasitized compared to those without flight muscles and those that were parasitized contained predominantly eggs and first instar larvae The results were compared with other Microctonus biocontrol agents released in New Zealand and it was concluded that passive dispersal should play a major role in dispersing Irish M aethiopoides in New Zealand especially in warm dry summers